The Australian Institute of Archaeology and the beginning of ancient world archaeology at the University of Melbourne - Davey, Christopher J. (Buried History: The Journal of the Australian Institute of Archaeology, 2024)
The origin of the relationship between the University of Melbourne and the Australian Institute of Archaeology is described together with the roles played by Maurice Goldman and John Thompson. The circumstances of William Culican’s arrival in Melbourne are discussed, and the expectations of the founder of the Institute, Walter Beasley, in relation to Thompson and Culican are briefly explored.